Evaluasi Pedestrian untuk Meningkatkan Kenyamanan Fisik dan Psikologis di Kota Bogor - Rahmah, Fannia Aulia; Arifin, Hadi Susilo; Nurhayati (Jurnal Lanskap Indonesia, 2026)
Prioritizing the comfort and safety of pedestrian paths can increase pedestrian volume, reduce dependence on motorized vehicles, and contribute to sustainable urban development. However, pedestrian-oriented transportation planning is often overlooked. This study evaluates the landscape of pedestrian walkways along Jalan Raya Pajajaran a national road with high levels of human activity and Jalan Sudirman the oldest road in Bogor. The evaluation focuses on walkway typologies, which are then assessed for compliance with the design requirements stated in the Regulation of the Minister of Public Works that concern guidelines for the planning, provision, and utilization of pedestrian infrastructure and facilities, based on land use categories. The research method employed is descriptive analysis, with data obtained through field surveys and literature studies. The research findings reveal fifteen distinct typologies of pedestrian pathways, each characterized by varying widths and surface materials. The physical comfort condition of pedestrian paths in Bogor City predominantly falls into the moderate quality category. The analysis highlights safety and the availability of shading facilities as two critical issues requiring immediate attention. Pedestrian pathways in Bogor are positioned in a strategic yet vulnerable spot. This indicates that the pedestrian infrastructure falls under the “Grow & Build Strategy” category.